Pengaruh Kekuatan Otot Lengan Dan Kelentukan Pinggang Terhadap Forehand Smash Dalam Permainan Tenis Meja - Rahmat, Rahmat; Komaludin, Dudi (Jurnal Performa Olahraga, 2022)
This research is motivated by the still low ability of forehand smash or extracurricular punch forehand participants in table tennis year in SD Negeri Penanggapan 03. This study aims to determine the effect of arm muscle strength and waist flexibility on forehand smash skills in men's table tennis extracurricular at SD Negeri Penanggapan 03. The population of this study were 21 table tennis extracurricular participants. Retrieval of data using a test with the ability instrument forehand smash skills. Data analysis techniques using the F-test, through the prerequisite tests of normality and hypothesis. The results of hypothesis testing using the F-test the effect of arm muscle strength on forehand smash skills with the F Test between F arithmetic 5.165> F table 4.35 influences 21.4%, the effect of waist flexion on forehand smash skills with the F Test between F arithmetic 9.314> F table 4.35 has an effect of 32.9%, and the influence of arm muscle strength and waist flexion on forehand smash skills with the F Test between F arithmetic 5.464> F table 3.53 has an effect of 37.8%. From these results it can be concluded that there is an influence of arm muscle strength and waist flexion on forehand smash skills in men's table tennis extracurricular at Penanggapan 03 Public Elementary School.